(untitled) (Research, Society and Development, 2020)
Young vegetables are gaining more and more popularity on a world scale, not only because they are highly nutritious foods, but because they constitute a new ingredient, being used to improve the visual aspect of salads and other garnishes and to embellish a wide variety of dishes. This study aimed to compare the content of bioactive compounds and the antioxidant capacity of kale (Brassica oleracea L.) in three growth stages: microgreen (15 days after sowing), baby leaf (40 days after sowing) and adult (60 days after sowing). The cultivation was carried out in trays for the production of microgreens, later a portion was transplanted in beds to obtain baby leafs and plants in an adult stage. The analyzes performed were: total carotenoids, mineral profile, phenolic compounds and antioxidant capacity. Chemical analyzes showed, in general, that vegetables in microgreens and baby leaf stages had higher levels of micronutrients and antioxidant capacity by the phosphomolybdenum method than the plant in the adult (commercial) stage, however, for phenolic compounds and total carotenoids, the adult plant had higher levels than baby leaf and microgreens. It should be noted that baby leaf and microgreens are usually eaten raw and whole, avoiding losses and obtaining a better use of nutrients present in these vegetables. Thus, the consumption of vegetables harvested at early stages may contribute to a greater supply of nutrients and bioactive compounds in the diet.